1999
DOI: 10.1002/(sici)1096-987x(19991115)20:14<1527::aid-jcc5>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Comparing search strategies for finding global optima on energy landscapes

Abstract: ABSTRACT:We provide some tests of the convex global underestimator Ž . CGU algorithm, which aims to find global minima on funnel-shaped energy landscapes. We use two different potential functions-the reduced Lennard᎐Jones cluster potential, and the modified Sun protein folding potential, to compare the CGU algorithm with the simplest versions of the traditional Ž . trajectory-based search methods, simulated annealing SA , and Monte Carlo Ž . MC . For both potentials, the CGU reaches energies lower on the lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Cootes et al found that such methods speeded the Monte Carlo search, provided more accurate estimates of global optima for known test cases, but were not as fast as mean-field methods. Foreman et al developed a new global optimization method which works well for rugged energy surfaces with an overall funnel topology . Such methods may eventually prove useful for protein design.…”
Section: Search Methodsmentioning
confidence: 99%
“…Cootes et al found that such methods speeded the Monte Carlo search, provided more accurate estimates of global optima for known test cases, but were not as fast as mean-field methods. Foreman et al developed a new global optimization method which works well for rugged energy surfaces with an overall funnel topology . Such methods may eventually prove useful for protein design.…”
Section: Search Methodsmentioning
confidence: 99%
“…The search space contains a large number of equivalent solutions because there are N ! ways to order the N atoms in any local minima [8]. The 38 atoms test problem is particularly interesting because it has been shown to be more difficult than larger clusters because it has two very competitive solutions that have a distinctly different atomic structure [6] resulting in two distinct clusters of local optima.…”
Section: Related Workmentioning
confidence: 99%
“…First, knowledge of landscapes will be of benefit in designing faster and more robust computer methods for predicting native structures (6,7). Second, a goal of computational biology is not just to predict native structures, per se, but to predict function.…”
mentioning
confidence: 99%